2018
DOI: 10.1016/j.jds.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Abundant proteins in platelet-rich fibrin and their potential contribution to wound healing: An explorative proteomics study and review of the literature

Abstract: Background/purpose It is well-known that diverse types of blood proteins contribute to healing process via different mechanisms. Presence and potential involvements of blood-derived abundant proteins in the platelet-rich fibrin (PRF) to its regenerative capacity have not been sufficiently emphasized in the literature. The aim of this paper was to analyze the abundant proteome content of PRF and summarize previously reported effects of identified proteins on wound healing via a literature review. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 93 publications
2
13
0
3
Order By: Relevance
“…For instance, multiple APPs showed significant elevation in the plasma of patients with more severe outcomes. Among them, CRP, ORM1, ORM2, and SERPINA3 are inflammatory factors that are controlled by multiple cytokines, such as interleukin-1b (IL-1b), tumor necrosis factor-a (TNF-a), IL-6, and IL-6-related cytokines (Ceciliani and Lecchi, 2019;Cichy et al, 1995;Fournier et al, 2000;Luo et al, 2015;Tyagi et al, 2013;Yaprak et al, 2018), although S100A9 and its partner S100A8, also identified here, can induce inflammatory cytokines and immune cell migration (Wang et al, 2018). Moreover, S8 and S9.…”
Section: Llmentioning
confidence: 68%
“…For instance, multiple APPs showed significant elevation in the plasma of patients with more severe outcomes. Among them, CRP, ORM1, ORM2, and SERPINA3 are inflammatory factors that are controlled by multiple cytokines, such as interleukin-1b (IL-1b), tumor necrosis factor-a (TNF-a), IL-6, and IL-6-related cytokines (Ceciliani and Lecchi, 2019;Cichy et al, 1995;Fournier et al, 2000;Luo et al, 2015;Tyagi et al, 2013;Yaprak et al, 2018), although S100A9 and its partner S100A8, also identified here, can induce inflammatory cytokines and immune cell migration (Wang et al, 2018). Moreover, S8 and S9.…”
Section: Llmentioning
confidence: 68%
“…Interestingly, Anitua et al 17 also found acute phase response and LXR/RXR between the top ten canonical pathways in the analysis of the proteins extracted with acetonitrile from their PRC. The presence of abundant proteins related to acute phase response such as fibrinogen, albumin, and complement cascade factors were also identified in the secretome and the lysates of other PRC 17,20,21 . In our study, clathrin mediated endocytosis is the most represented pathway mostly due to the presence of growth factors identifications such as PDGF and EGF in the L-PRF secretome.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies have used different approaches to analyse the proteome of different PRC, although all of them were obtained using anticoagulants 17,21 . Indeed, Yaprak et al analysed the PRF secretome by 2D-LC/ MS-MS finding a low number of identifications, only 35 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A irradiação de luz nos tecidos biológicos com objetivo fotoquímico, dentro da banda vermelhoinfravermelho, apresenta diversas alterações no metabolismo celular, modicando a viscosidade da água intracelular, a convenção transmembranosa e provendo maior formação de adenosina trifosfato e supressão dos radicais livres 9 .…”
Section: Discussionunclassified